Potential of Local Ebony Wood Products Processing in Mantikulore District, Palu, Indonesia - Rukhayati; Abdul Rahman; Andi Sahri Alam; Rafiuddin (Jurnal Penelitian Pendidikan IPA, 2025)
This research aims to deepen knowledge and develop knowledge about ebony wood, as well as to provide solutions to the problems faced by the community in Mantikulore District, one of the centers of the ebony wood industry in Palu. The ebony wood industry has significant potential to create added value, create jobs, and improve community welfare by processing local products into various types of finished goods. This research employed an interactive, qualitative descriptive method, with data collection techniques including direct field measurements, interviews, participant observation, and Focus Group Discussions (FGDs). Secondary data were obtained from statistics, official documents, research reports, and relevant literature. The results indicate that ebony wood processing can increase added value and create new jobs for the community. The ebony wood craft industry also encourages independence by utilizing local creativity and skills. This research involved the Central Sulawesi Provincial Tourism Office, the Central Sulawesi Provincial Forestry Office, and MSME observers, and aimed to improve community welfare. The implications of this research are that it provides valuable input for the formulation and implementation of ebony wood industry development policies and contributes to the optimal utilization of resources and funds. The FGD results indicated that MSMEs hoped for training to broaden their knowledge and skills, while the Tourism Office hoped to increase the added value of ebony craft products. A possible solution for MSME observers is to include ebony craft MSMEs in the banking funding database as a form of government support and incentive.